2015
DOI: 10.1016/j.juro.2014.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Serum miRNA (miR-367-3p, miR-371a-3p, miR-372-3p and miR-373-3p) as Biomarkers in Patients with Testicular Germ Cell Cancer

Abstract: miR-371a-3p allows for better identification of testicular germ cell tumor than α1-fetoprotein and human chorionic gonadotropin. It could be helpful for clinically managing testicular germ cell tumor, especially for monitoring surveillance therapy and residual disease after chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
115
2
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 168 publications
(140 citation statements)
references
References 24 publications
9
115
2
4
Order By: Relevance
“…Tests targeting these specific miRNAs are currently under development. Preliminary studies have already proven great specificity (99-100%) and sensitivity of these tests for the detection of TGCT [100][101][102]. Other body fluids are also suitable for detection of miRNA released by disseminated tumours, e.g.…”
Section: Traces Of Gct In Blood: Classical Biochemical Markers and MImentioning
confidence: 99%
“…Tests targeting these specific miRNAs are currently under development. Preliminary studies have already proven great specificity (99-100%) and sensitivity of these tests for the detection of TGCT [100][101][102]. Other body fluids are also suitable for detection of miRNA released by disseminated tumours, e.g.…”
Section: Traces Of Gct In Blood: Classical Biochemical Markers and MImentioning
confidence: 99%
“…130 Subsequently, the expression levels of these tissue-based signatures were measured in serum. [131][132][133][134][135][136] These liquid biopsy data confirmed the potential utility of miRNA measurements for discriminating patients with seminoma or those with nonseminoma from healthy control subjects. A selected set of four miRNAs (miR-371a-3p, miR-372, miR-373 and miR-367) present in the two clusters that showed the highest discriminative power for diagnosis and follow-up of cancer, combined with reference miRNAs (miR-20a and miR-93) and spike-in controls was developed as the 'targeted serum miRNA assay' (TSmiR).…”
Section: [H1] Biofluid Micrornas In Testicular Cancermentioning
confidence: 67%
“…134,136 Two independent studies, confirmed these promising results for miR-371a-3p as a biomarker for testicular cancer; however these reports only included a limited number of participants. 132,133 A simplified assay for analysing miR371a-3p without endogenous controls was recommended to reduce laboratory work, analytical time and costs. 137 Results of another study confirmed the discriminative ability of serum miR-371a-3p and miR-372 concentrations and also identified numerous novel discriminative serum miRNAs (miR-511, miR-26b, miR-769, miR23a, miR-106b, miR-365, miR-598, miR-340 and let-7a), which were identified using a high-throughput profiling system, but did not validate the results.…”
Section: [H1] Biofluid Micrornas In Testicular Cancermentioning
confidence: 99%
“…Our own data also confirm the improved sensitivity (85%) and specificity (99%) of miR-371 when compared to AFP (14%) and HCG (37%). 9 In summary, several independent studies indicate an increase of miR-371-373 in TGCT patients irrespective of their histological subtypes and, therefore, result in a better diagnostic performance than AFP/HCG.…”
Section: Nucleic Acids Micrornamentioning
confidence: 91%